ISOLASI FUNGI ENDOFIT DAUN Srikaya (Annona muricata L.) SEBAGAI ANTIOKSIDAN SECARA KLT-AUTOGRAFI - Asri, Muhammad Ikhwan; Sabaruddin, Sabaruddin; Fitriana, Fitriana (Journal Microbiology Science, 2021)
Antioxidants are compounds that can neutralize free radicals that produced by endophyte microbes. This study aims to isolate endophyte fungi and antioxidant activity of isolate endophyte fungi of Annona muricata L. leave used TLC-Autograph Method. The result of isolation endophyte fungi  Annona muricata L. leaves obtained 7 isolates namely FES1, FES2, FES3, FES4, FES5, FES6, dan FES7 colonies. Isolates of endophytic fungi were purified by quadran steak method to obtain pure isolates. The pure isolates obtained were fermented in Maltosa Yeast Broth (MYB) medium using shaker at 200 rpm for 7 x 24 hours to obtain secondary metabolites namely mycelia and supernatant. The results of testing the antioxidant activity of the supernatant extract of endophytic fungi isolates by TLC-Autograph using 0.04% DPPH spray reagent showed that the endophytic fungi isolate FES2 had free radical activity at Rf values of 0.94 and 0.87.